HAMKA'S PHILOSOPHY OF VALUES RELEVANCE AND CONTEMPORARY CHALLENGES IN MODERN INDONESIA - Saragih, Ismawati (Program Doktor Akidah dan Filsafat Islam, 2025)
This article examines the concept of values according to Hamka (1908-1981), a prominent Islamic scholar, litterateur, and philosopher in Indonesia. Drawing from his intellectual legacy, this study explores the definition of values, their sources, hierarchy, and their application in contemporary Indonesian society. Hamka emphasizes the primacy of religious, moral, and ethical values as the foundation for human conduct and character formation. The analysis reveals that while Hamka's teachings remain highly relevant to Indonesia's current socio-religious context particularly regarding moderation, integrity, work ethics, and nationalism significant challenges impede their practical implementation. These obstacles include pervasive individualism, consumerist behavior, the erosion of religious and moral values, the influence of foreign cultural paradigms, and the scarcity of exemplary figures. This study argues that revitalizing Hamka's philosophical framework is essential for constructing a more dignified and prosperous Indonesian society. Through critical examination of both the enduring relevance and contemporary obstacles, this article contributes to the broader discourse on value systems in Islamic-majority societies navigating modernization.